2021
DOI: 10.1016/j.xcrm.2021.100194
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of neo-epitope immunogenicity reveals TCR recognition determinants and provides insight into immunoediting

Abstract: Summary CD8+ T cell recognition of peptide epitopes plays a central role in immune responses against pathogens and tumors. However, the rules that govern which peptides are truly recognized by existing T cell receptors (TCRs) remain poorly understood, precluding accurate predictions of neo-epitopes for cancer immunotherapy. Here, we capitalize on recent (neo-)epitope data to train a predictor of immunogenic epitopes (PRIME), which captures molecular properties of both antigen presentation and TCR re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
205
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 114 publications
(220 citation statements)
references
References 85 publications
13
205
2
Order By: Relevance
“…Data were indexed, integrated, and scaled in HKL2000. The SILv44-WT peptide/HLA-A2 structure was solved using the Phaser molecular replacement module in PHENIX using the TCR and peptide/HLA-A2 from the SILv44-T2Met/HLA-A2 structure as separate search models (34). The initial search model for the T4H2 TCR was built with Sculptor in PHENIX using the α-chain of Protein Data Bank (PDB) 3QEU and the β-chain of PDB 4C56 (59,60).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Data were indexed, integrated, and scaled in HKL2000. The SILv44-WT peptide/HLA-A2 structure was solved using the Phaser molecular replacement module in PHENIX using the TCR and peptide/HLA-A2 from the SILv44-T2Met/HLA-A2 structure as separate search models (34). The initial search model for the T4H2 TCR was built with Sculptor in PHENIX using the α-chain of Protein Data Bank (PDB) 3QEU and the β-chain of PDB 4C56 (59,60).…”
Section: Methodsmentioning
confidence: 99%
“…The PDB IDs for the structures determined here are 6VMC (T4H2-T2Leu/A2), 6VM9 (T4H2-T2Met/A2), 6VMA (T4H2-WT/A2), and 6VM7 (SILv44-WT/A2). The PDB ID of the separately determined SILv44-T2Met/A2 structure used for comparison is 6VM8 (34). equilibration as is standard.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We addressed this by analyzing the neoepitopes that were products of AID activity on the TCGA cohort and on melanoma patients treated with Nivolumab (anti-PD-1) (Riaz et al, 2017). A recent bioinformatic-experimental study using immunogenic and non-immunogenic peptides, experimental testing and X-ray structures showed that TCR binding and recognition improves with the presence of hydrophobic amino acids (aromatic W, F, Y followed by V, L and I) at specific “MIA’’ positions (position P 4 -P 1-Ω ) due to increased structural avidity, stacking interactions, hydrogen bond acceptance and limited rotational freedom with the TCR (Schmidt et al, 2021). Additionally, as a previous study showed that APOBEC promiscuous activity increases neopeptide hydrophobicity (Boichard et al, 2018), we wondered if AID-related mutations led to the production of not only more hydrophobic neoepitope but more “Immunogenic” in terms of amino acid changes (W, F, Y, V, L, I over others) at MIA positions and if these effects were different due to clonality, histology or mutational processes.…”
Section: Resultsmentioning
confidence: 99%
“…To account for immunogenicity based on prediction of neopeptide TCR recognition and neopeptide HLA binding, PRIME software was run with default parameters. Neoepitopes were classified as “Immunogenic” if having a PRIME %rank score (the fraction of random 700,000 8- to 14-mers that would have a score higher than the peptide provided in input) lower or equal to 0.5% for the corresponding HLA haplotype of the patient where the neopeptide occurred, or as “Non-Immunogenic” otherwise (Schmidt et al, 2021). For simplicity some cosmic signatures were grouped together as: MMR (SBS6, SBS15, SBS20, SBS21, SBS 26 and SBS44); Smoking-associated (SBS4, SBS18, SBS24 and SBS29); POLE (SBS10a, SBS10b and SBS14) and APOBEC (SBS2 and SBS13).…”
Section: Methods Detailsmentioning
confidence: 99%